Characteristics, Antioxidant, and Antihypertensive Activities of Probiotic Greek Yogurt with Roselle Extract Addition - Juandini, P. A.; Arief, I. I.; Wulandari, Z.; Abidin, Z. (Tropical Animal Science Journal, 2024)
Yogurt is one example of a functional food that can improve health and reduce the risk of diseases. Certain ingredients, such as probiotic bacteria and roselle extract, are added to yogurt to enhance its benefits. The utilized probiotic, Lactobacillus plantarum IIA-1A5, provides notable antimicrobial benefits. Additionally, the incorporated roselle extract is established to possess antioxidant and antihypertensive properties. This study aims to analyze the characteristics, antioxidant, and antihypertensive activities of probiotic Greek yogurt (PGY) and probiotic Greek yogurt with roselle extract (PGYR). The roselle extract added to the Greek probiotic yogurt was 3%, and the bacteria used in the fermentation process for both treatments were S. thermophilus IFO 13957, L. bulgaricus IFO 13953, and L. plantarum IIA-1A5. Each treatment was replicated three times in duplicate. The results showed that the addition of roselle extract to probiotic Greek yogurt significantly influenced (p<0.05) the antioxidant and antihypertensive activity, water activity (aw), pH, total acidity (TAT), and the color aspect in the hedonic test and the flavor, color, and aroma aspects in the hedonic quality test. The antioxidant activity and antihypertensive activity tests yielded significantly different results. The antioxidant activity increased from 29.32% (PGY) to 44.93% (PGYR), while the antihypertensive activity increased from 35.68% (PGY) to 81.36% (PGYR). This study concluded that the characteristics of PGYR have met the SNI standards and have a higher antioxidant and antihypertensive activity value than PGY. PGYR also has a promising potential for commercial development due to its health benefits.